TWO ROMAN DICE FROM THE MOLDAVIAN PLAIN - Daniel Ciucălău (Journal of Ancient History and Archaeology, 2017)
The article presents two  Roman long dice discovered in the carpic settlements from Botosani-Dealul Cărămidăriei and Botosani-Groapa lui Ichim Their presence attests to the diversity of the relations between the free Dacians from the Plain of Moldavia and the Roman world of the 3rd century.